Effect of Supraperiosteal Injection of Dexamethasone on Interappointment Pain in Teeth with Symptomatic Irreversible Pulpitis: A Comparative Study - Lt Col Ajmal Yousaf; Fatima Ali; Syed Muzammil Hussain; Faisal Bhangar; Nasrin Yousaf; Khurshid Ali Bangash (Life and Science)
Objective: To compare the effect of supraperiosteal injection of dexamethasone with 2% lidocaine on the frequency of interappointment endodontic pain at different time intervals. Study Design: Prospectivecomparativestudy. Place and Duration of Study: The study was carried out at operative department of Armed Forces Institute of Dentistry, Rawalpindi from 1st October 2019 to 31st March 2020. Materials and Methods: A total of 100 patients presenting to the Department of Operative Dentistry, Armed Forces Institute of Dentistry, Rawalpindi and giving consent for participation, aged 20-50 years from both genders, presenting with acutely inflamed pulp in their maxillary first molars were selected for this study using convenient sampling technique. The patients were randomly divided into two equal groups of 50 patients with the help of scientific random number table. Endodontic therapy was initiated, pulpectomy canals were prepared with ProTaper Next system, intra-canal dressings of calcium hydroxide were placed and the cavity was restored with Cavit till the next appointment. Group A patients were then injected with dexamethasone at the mucobuccal fold and group B patients were injected with lidocaine used as placebo. Pain was recorded at 48 and 72 hours using the visual analogue scale. Data was analyzed using SPSS 21. Results: The study included equal number of male and females. The mean age of group A was 35 ± 4.5 years while of group B was 33 ± 6.7 years. The results showed that dexamethasone does not reduce pain at 48 and 72 hours compared to the placebo. Conclusion: It is concluded that dexamethasone does not reduce interappointment endodontic pain when compared to a placebo.